Deletions in guaBA and htrA but not clpX or rfaL constitute a live-attenuated vaccine strain of Salmonella Newport to protect against serogroup C2-C3Salmonella in mice. Issue 6 (3rd June 2019) - Fuche, Fabien J.; Jones, Jennifer A.; Ramachandran, Girish; Higginson, Ellen E.; Simon, Raphael; Tennant, Sharon M.
ABSTRACT: Non-typhoidal Salmonella (NTS) are a leading cause of foodborne infections worldwide, and serogroups B, C1, C2- C3 and D are the most common serogroups associated with human disease. While live vaccine candidates that protect against S. Typhimurium (serogroup B) and S. Enteritidis (serogroup D) have been described by us and others, far less effort has been directed towards vaccines that target either serogroup C1 or C2- C3 Salmonella . Here we describe a Salmonella Newport-based live-attenuated vaccine (serogroup C2- C3 ). Deletion of the genes clpX or rfaL, previously used in live vaccines to attenuate S. Typhimurium and/or S. Enteritidis, failed to attenuate S. Newport. However, we found that deletion of either guaBA or htrA raised the 50% lethal dose of S . Newport in an intraperitoneal infection model in BALB/c mice. Our live-attenuated vaccine candidate CVD 1966 ( S. Newport Δ guaBA Δ htrA ) elicited strong antibody responses against COPS, flagellin and outer membrane proteins when administered intraperitoneally or orally. Following lethal challenge with the parental virulent strain of S . Newport, we observed vaccine efficacies of 53% for immunization via the intraperitoneal route and 47% for immunization via the oral route. Following intraperiteonal immunization, the vaccine also significantly reduced the bacterial burden of challenge organisms in the liver and spleen. Interestingly, reducing the LPS chain length by deleting rfaL did not induce a stronger immune response towards surface antigens, and failed to elicit any protection against lethal homologous challenge. In conclusion, we have developed a live-attenuated Salmonella serogroup C2- C3 vaccine that we are further evaluating.